PENGARUH SISTEM INFORMASI MANAJEMEN DAN LINGKUNGAN KERJA TERHADAP KINERJA TENAGA KEPENDIDIKAN PADA UNIVERSITAS KATOLIK SANTO THOMAS - Situmorang, Theresa Sisilia; Gultom, Parapat (Jurnal Manajemen dan Bisnis, 2024)
This study entitled "The Influence of Management Information System and Work Environment on Educational Staff Performance at University of Saint Thomas Sumatera Utara". The purpose of this study was to determine the effect of Management Information System and Work Environment on Educational Staff Performance. This research method is descriptive research, hypothesis testing using multiple regression analysis. Data processing is done using SPSS. The population in this study were 78 educational staffs. In this study, sampling using the slovin formula, the number of samples in this study was 42 people. Based on the F test, it is known that the influence of the management information system and work environment on the performance seducational staff, together has a significant effect on the performance of staff. Based on the t test, it is known that the management information system has a positive and significant effecton the performance of educational staff and work environment has a positive and significant effecton the performance of educational staff. Based on the results of multiple linear regression, it is known that the variable that has the greatest influence on the performance of educational staff University Saint Thomas, Sumatera Utara is the work environment, which is 16,8 percent.